Distribution patterns of blue whale (Balaenoptera musculus) and shipping off southern Sri Lanka - Priyadarshana, T.; Randage, S.M.; Alling, A.; Calderan, S.; Gordon, Jonathan Charles David; Leaper, R.; Porter, L. (Regional Studies in Marine Science, 2015)
Surveys were conducted off the southern coast of Sri Lanka in 2014 and 2015 to investigate the distribution patterns of blue whales (Balaenoptera musculus spp.) in relation to current shipping lanes, and further offshore. There have been several reported ship strikes of blue whales in this area and the IWC Scientific Committee has recognised the potential for ship strikes to have population level impacts on blue whales in the northern Indian Ocean. A total of 3268km of visual survey effort was conducted on 35 survey days along north-south transects between 5°28'N and 5°53'N. These data were used to model patterns of whale density. The highest densities of blue whales were observed in the current shipping lanes, peaking at an average of 0.1 individuals km -2 along the westbound shipping lane. Automatic Identification System transmissions received by satellite were used to estimate shipping density. Between 80°30'E and 81°E, the peak mean shipping density in the westbound lane of the Traffic Separation Scheme was 1090km -1 year -1 and in the eastbound lane 810km -1 year -1 . These high densities of whales combined with one of the busiest shipping routes in the world suggest a severe risk of ship strikes. Previous data on blue whale distribution and coastal upwellings indicate consistent and predictable patterns of whale distribution, suggesting there is considerable potential for effective measures to keep ships and whales apart. For example, data from this study would suggest risk could be reduced by 95% if shipping were to transit 15 nm further south than currently.